2013
DOI: 10.1002/jor.22351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiation and surgery on healing of femoral fractures in a rat model

Abstract: Management of soft tissue sarcoma involves multimodality treatment, including surgery and radiotherapy. Pathologic fracture of the femur after such treatment in the thigh is one serious, late complication and nonunion rates of 80-90% are reported. We hypothesize that the combination of radiotherapy and periosteal stripping (during tumor resection) leads to greater impairment of the fracture repair process than either intervention alone. Female Wistar retired breeder rats were randomized into four treatment gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 41 publications
2
19
0
2
Order By: Relevance
“…A remarkably increased incidence of delayed and nonunion fracture within a prior irradiated bone has been a well‐known clinical observation for many years. Several previous rodent studies reported that radiation before or immediately after fracture causes alterations in the histology and radiology of the reparative processes . However, all those studies used whole‐body radiation, which limited the local radiation dosage that could be applied and was always accompanied by systematic effects, which primarily affect hematopoiesis and had abscopal effects on radiation‐shielded bones .…”
Section: Discussionmentioning
confidence: 99%
“…A remarkably increased incidence of delayed and nonunion fracture within a prior irradiated bone has been a well‐known clinical observation for many years. Several previous rodent studies reported that radiation before or immediately after fracture causes alterations in the histology and radiology of the reparative processes . However, all those studies used whole‐body radiation, which limited the local radiation dosage that could be applied and was always accompanied by systematic effects, which primarily affect hematopoiesis and had abscopal effects on radiation‐shielded bones .…”
Section: Discussionmentioning
confidence: 99%
“…Since these were all low-energy fractures located within the irradiated surgical field, altered bone biology is likely to be the cause. 14 Cao et al 15 reported that irradiated mouse femora had fewer mesenchymal stem cells, osteoblasts and osteoclasts, blood vessels were destroyed and the number of free radicals increased. The rates of nonunion of radiation-induced fractures stand in stark contrast to typical traumatic fractures of the femur that have a rate of nonunion < 3%.…”
Section: Discussionmentioning
confidence: 99%
“…The bulb tube parameters were 50–55 kV and 5–10 mAs. The fracture union was defined as the presence of a bridged callus in at least three of four cortices on two radiographic views45.…”
Section: Methodsmentioning
confidence: 99%
“…As in previous publications, the mineralized tissues were classified as bone or callus depending on its density relative to that of the undisturbed cortical bone45. A callus was defined as bone having a density of 35–70% of the maximum density of the undisturbed cortical bone.…”
Section: Methodsmentioning
confidence: 99%